THE DISCOURSE OF BALI’S FAMILY PLANNING: - Kumbara, A.A. Ngurah Anom; Dewi, A.A. Sagung Kartika (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
This paper intends to critically analyze the Bali’s family planning discourse that was launched by the Governor of Bali in June 2019, which gave rise to pros and cons in the community. State hegemony through the national KB program 'Two Enough Children' is seen to have weakened the demographic position of the ethnic Balinese on the one hand and the dominance of the migrant population on the other. The purpose of this study is to explain how ideological interests, political interests of identity, and cultural romanticism operate and contest in the discourse of Bali’s family planning in Bali. Using the critical discourse analysis method this study found that Bali's family planning discourse involves the contestation of local, national, and global ideologies. His conclusion was that in the contestation the practice of identity politics and the manipulated of cultural romanticism by subjects and actors took place in the dialectics of competition and positioning between Balinese and migrant populations.